2008
DOI: 10.1111/j.1365-294x.2008.03753.x
|View full text |Cite
|
Sign up to set email alerts
|

Multigene analysis suggests ecological speciation in the fungal pathogen Claviceps purpurea

Abstract: Claviceps purpurea is an important pathogen of grasses and source of novel chemical compounds. Three groups within this species (G1, G2, and G3) have been recognized based on habitat association, sclerotia and conidia morphology, and alkaloid production. These groups have further been supported by RAPD and AFLP markers, suggesting this species may be more accurately described as a species complex. However, all divergent ecotypes can coexist in sympatric populations with no obvious physical barriers to prevent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 89 publications
(156 reference statements)
2
37
0
1
Order By: Relevance
“…Previous host specificity studies involved inter-and intraspecific hybridizations of fungal pathogens (15,36). However, despite the potential importance of ecological factors driving genetic divergence, they are poorly understood in fungi (18,22,32,33), and most of the existing data have been obtained from highly artificial experiments (18). In our work, the differences between the two parental isolates included both pathogenic fitness (RAUDPC and incubation period) and temperature adaptation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous host specificity studies involved inter-and intraspecific hybridizations of fungal pathogens (15,36). However, despite the potential importance of ecological factors driving genetic divergence, they are poorly understood in fungi (18,22,32,33), and most of the existing data have been obtained from highly artificial experiments (18). In our work, the differences between the two parental isolates included both pathogenic fitness (RAUDPC and incubation period) and temperature adaptation.…”
Section: Discussionmentioning
confidence: 95%
“…), Claviceps purpurea (Douhan et al. ), Venturia inaequalis (Gladieux et al. ), fungal endophyte Colletotrichum gloeosporioides agg.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained after crossing of two C. purpurea strains showed that single copy RAPD fragments segregate in a 1:1 ratio, and therefore can be used as genetic markers [18]. It was shown that data from RAPD as well as AFLP analyses were more informative than DNA sequences (i.e., β-tubuline gene or ITS rDNA) for separating the different ecotypes [38].…”
Section: Discussionmentioning
confidence: 98%